The Principles of Sustainable Development and the Possibilities of Limiting the Global Effects of Smog by Medium-sized Cities Located in the European Union on the Example of Mikołów (Poland) and Żylina (Slovakia) - Czuba, Michał (Problemy Ekorozwoju, 2020)
The urban smog has negative global effects. They are expressed in the increased mortality of people, an increase scale of respiratory diseases as well as climate changes causing negative effects in the field of agricultural crops, which results in an increase in food prices. The occurrence of these phenomena mobilizes the global community to conduct activities aimed at limiting their occurrence. Medium-sized cities can play a significant role in this respect. The element conditioning the life of city dwellers is the appropriate condition of the natural environment. In Polish and Slovak conditions, smog is becoming a problem, which negatively affects the health of citizens of these countries. Therefore, actions are taken to limit the occurrence of this phenomenon. They are described in the current ecological policy of both countries. This article tries to show on the example of the Polish commune of Mikołów and the Slovak commune of Żylina the actions taken in them to reduce air pollution and thereby reduce the phenomenon of smog. In both analysed cities, measures taken to reduce the phenomenon of smog are implemented in a planned manner and may be an inspiration for other medium-sized cities in the world having air quality problems.